A new host record of Diaporthe rosae on Rambutan (Nephelium lappaceum L.) - Huanraluek, Naruemon; Phunyaboon, Wilawan; Jayawardena, Ruvishika S. (Phytotaxa, 2022)
Rambutan (Nephelium lappaceum L.) is one of the most popular tropical fruits in Thailand. There is less number of studies associated with rambutan associated fungi in Thailand. During a survey to identify fungi associated with rambutan we identified D. rosae using multi-locus phylogeny (ITS-tub2-tef1-α-cal) and morphology. In this study, we provide the first report of Diaporthe rosae associated with branches of N. lappaceum in Thailand and in the world. This study provides a new host and a distribution record of D. rosae with an aim of promoting future studies in plant pathology. Identification of potential plant pathogens can help the rambutan growers to take precautions and control the disease at an early stage.